A Two Sector Endogenous Growth Model with Two Accumulating Factors- Implementing Trade - Birgit Kirschbaum (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper is about trade in an endogenous growth model with accumulation of physical and human capital. The convergence to the ray of steady states is proved for two different development stages of similar small countries. Free trade benefits the education sector of a relatively less developed country and thus stimulates the human capital accumulation. Whereas a technological more developed country declines in favour of the world market. Only if the small country is relatively less developed then there is a convergence to the balanced growth path of the world market and the country improves its situation. Without any trade policy a less developed country will lose necessary factors of production. A more developed country deals with stagnation or even fluctuation of its development stage.
Keywords: O11; F19; D51; 330